Entre règles et narration : étude narratologique des tutoriels de jeu vidéo et des « personnages-guides » - Fanny Barnabé (Cahiers de Narratologie)
This paper proposes to study video game tutorials from a narratological and rhetorical perspective. More precisely, it focuses on the case of the “guiding-characters”, these narrative incarnations of the tutorial that accompany the avatar’s progression by dictating to the player the steps to follow at each stage of the game. These hybrid beings represent an ideal entry point for studying the narrativization mechanisms of the rules at work within the medium, since they combine a utilitarian function (they reveal the game’s instructions) and a narratological function (they advance the narrative). Through the analysis of a series of examples, this research will aim to demonstrate that guiding-characters question three fundamental criteria used to define the concept of character: the presence of a media signifier, the integration of the character in a fictional universe and the fact that characters are human-like. In order to describe precisely how they escape these definitional frameworks, we will first distinguish two main categories of guiding-characters: interfacial characters and tutorial avatars. Secondly, we will discuss the narrative specificities of these entities: by mediating between the game universe and the player’s empirical gesture, they are indeed intrinsically metaleptic and they therefore do not exist on the same plane as the other characters. On the basis of this observation, we will differentiate tutorial avatars according to the rhetorical strategies they employ to negotiate with their transgressive nature: whether they conceal it (via tutorial metaphors), whether they leave it apparent (via raw metalepses) or whether they underline it (via fictionalized metalepses).